FREEDOM AND PRODUCTION OF KNOWLEDGE: ACADEMIC FREEDOM AND ITS FOUNDATIONS - Horácio Wanderlei Rodrigues (Universidade de Santa Cruz do Sul, 2019)
The purpose of this work is the principle of academic freedom, analyzed in the constitutional and infraconstitutional scope, indicating its possibilities and limits in relation to the fundamental right to education and the requirement to preserve pluralism of ideas, especially those resulting from the interaction between freedoms which comprises it (of teaching, unduly called freedom of teaching, of learning, of researching and of disseminating knowledge). Considering these questions, the article goes on to propose the adoption of the term academic freedom as the most appropriate and representative when referring to the various freedoms involved in educational processes and production of knowledge. It also concludes that the Federal Constitution contains academic freedom within the framework of the fundamental right to education and as an instrument of guaranteeing pluralism of ideas, not as freedom itself.